Assessing the potential impact of salidroside on Chikungunya virus-induced acute interstitial nephritis via network pharmacology, molecular docking and in vitro experiments - Cheng, Sheng; Xin, Jialiang; Zhang, Tianran; Zhang, Yulin; Ji, Chengxi; Kang, Lulu; Zhu, Xiangyu; Zhang, He; Wang, Wei; Liao, Xinfei (Frontiers in Cellular and Infection Microbiology, 2025)
Chikungunya virus (CHIKV) infection is often linked to acute interstitial nephritis (AIN) in fatal cases. Given the global spread of CHIKV and the lack of targeted antiviral treatments, there is an urgent need for effective therapeutic strategies against CHIKV-induced AIN. This study explored the therapeutic potential of salidroside (Sal) using an integrative approach involving network pharmacology, molecular docking and in vitro validation. Network pharmacology analysis identified 18 overlapping targets between Sal and AIN, including TNF, IL6 and AKT1. Molecular docking revealed strong binding affinities between Sal and key pathway proteins (Vina scores < –6), notably TNF, IL6 and BCL2. In vitro assays using CHIKV-infected 293T cells demonstrated that Sal (7.8125–2000 μM) enhanced cell viability by 8.9–25.9%, with the greatest effect observed at 1000 μM, without significantly altering viral replication. Mechanism analysis using the KEGG and FerrDB databases implicated apoptosis and ferroptosis in CHIKV-induced AIN pathogenesis. RT-qPCR analysis confirmed that Sal significantly downregulated ferroptosis-related genes (IL-6, IL-1β, SIRT1, PARP1, HMOX1) and apoptosis-associated markers (Bax, TNF-α, PARP1) in infected cells. Consistent with these findings, molecular docking demonstrated that Sal binds strongly to the ferroptosis-related protein GPX4 (Vina score: –6.3) and the apoptosis regulator NFKB1 (Vina score: –6.0). These results suggest that Sal is a promising therapeutic candidate for the treatment of CHIKV-induced AIN.